Heterozygosity-Rich Regions in Canine Genome: Can They Serve as Indicators of Balancing Selection? - Adrián Halvoník; Nina Moravčíková; Luboš Vostrý; Hana Vostra-Vydrova; Gábor Mészáros; Eymen Demir; Monika Chalupková; Radovan Kasarda (Animals)
Compared to the negative effect of directional selection on genetic diversity, balancing selection acts oppositely and maintains variability across the genome. This study aims to articulate whether balancing selection leads to heterozygosity-rich region islands (HRRIs) forming in the canine genome by investigating 1000 animals belonging to 50 dog breeds via 153,733 autosomal SNPs. A consecutive SNP-based approach was used to identify heterozygosity-rich regions (HRRs). Signals of balancing selection in the genome of studied breeds were then assessed with Tajima’s D statistics. A total of 72,062 HRRs with an average length of 324 kb were detected to be unevenly distributed across the genome. A total of 509 and 450 genomic regions were classified as HRRIs and balancing selection signals, respectively. Although the genome-wide distributions of HRRIs varied across breeds, several HRRIs were found in the same locations across multiple breeds. A total of 109 genomic regions were classified as both HRRIs and signals of balancing selection. Even though the genomic coordinates of HRRIs and balancing selection signals did not fully overlap across all genomic regions, balancing selection may play a significant role in maintaining diversity in regions associated with various cancer diseases, immune response, and bone, skin, and cartilage tissue development.